Austronea (Asparagaceae, Scilloideae), a new genus from southern Africa, including the description of seven new species - Martínez-Azorín, Mario; Crespo, Manuel B.; Alonso-Vargas, María Ángeles; Dold, Anthony P.; Pinter, Michael; Wetschnig, Wolfgang (Phytotaxa, 2018)
As part of a taxonomic revision of Urgineeae, combining morphological and genetic data from numerous samples from a large range of its distribution, here we describe Austronea, a new genus from South Africa and southern Namibia. This genus is related to Fusifilum based on general inflorescence and flower morphology, but it differs from it by the leaves usually leathery and sometimes thickened; the capitate to subcorymbose raceme commonly nodding at early developing stages; the reddish to green-yellowish tepals, rarely white (see flower buds), which are usually connate at the base to form a distinct cup and patent free lobes, rarely tepals nearly free from the base; the filaments linear to lanceolate, smooth or rarely papillate below; and the ovary green to yellow-orange. These differences are also supported by our genetic studies (not shown) in which Fusifilum and Austronea form two well supported sister clades. Seven new species of Austronea are described from South Africa and Namibia and 11 new combinations in the genus are presented. An identification key is provided for all 18 accepted species in the new genus.